Upaya Kementerian Kelautan dan Perikanan Indonesia Menangani Kasus IUU Fishing: M. V. Hai Fa 2014 – 2017 - Pamase, Fitriani Mutiara; Utomo, Tri Cahyo (Journal of International Relations, 2018)
In December 2014 the act of IUU Fishing occured in Papua waters conducted by Hai Fa motor vessel from China. Regarding this matter KKP made various efforts to resolve it and uphold the spirit of eradicating IUU Fishing. KKP has taken various efforts through national law by registration of the lawsuit to the Ambon District Court and appealed to the Maluku High Court as well as collaboration with other international organizations such as Interpol, IMO and the United Nations from 2014 to 2017. Responding to this, the study of this case aims to explain the various efforts taken by the KKP as well as the extent to which efforts can be carried out in handling the IUU Fishing case practiced by M. V. Hai Fa. Besides that the research also aims to describe the phenomenon of IUU Fishing in Indonesia as well as various driving and inhibiting factors in this case. This study uses the Regime Theory which links the procedures for handling IUU Fishing Hai Fa with regime expectations reinforced by the concept of non-conventional maritime sovereignty which focuses on economic, social and environmental areas doubled with the concept of maritime security which focuses on blue economy and human resilience which discusses economic sustainability, maritime ecosystem, food security for fisheries products and threats to the work of traditional fishermen. This study uses qualitative methods with descriptive research types that utilizes interview and literature sources. The final result of this study shows that the various efforts taken by the KKP in handling the M. V. Hai Fa case from 2014 to 2017 did not produce results in accordance with the KKP's expectations. Responding to this, KKP should bring the Hai Fa case to ITLOS if It want to pursue the case further.